2017
DOI: 10.24273/jgeet.2017.2.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Study of Boundary and Depth of the Soil Structure for Geotechnical Site Investigation using MASW

Abstract: This study reviews the correlation between the experimental Rayleigh dispersion curve and the Vp & Vs ground model versus depth. Six samples of stations A , B , C , D , E and F were used in the experiment.The geophone spacing used was set 1 m and total length of each line was 23 m. The result shows positive significance (best fit) of R2 that ranges from 0.80 to 0.90. The fk (frequency-wave number method) dispersion curves analysis confirmed that the soil structure investigated is divided into three zones: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Nilai kecepatan gelombang geser merupakan salah satu parameter untuk megetahui kondisi tanah serta memperkirakan bahaya gerakan tanah secara spesifik yang berdampak terhadap daya dukung tanah disekitar kawasan (Yusran,2021). Lapisan tanah dengan kepadatan rendah umumnya memiliki daya dukung yang rendah pula, sehingga rawan terhadap terjadinya penurunan pondasi bangunan (Arisona, 2017;Mustika dan Sriyani, 2019). Kajian dalam bentuk pemetaan lapisan tanah dengan menggunakan data Mikrotremor HVSR diperlukan untuk memperoleh gambaran tentang lapisan tanah yang berpotensi tinggi rawan terhadap guncangan gempa bumi.…”
Section: Pendahuluanunclassified
“…Nilai kecepatan gelombang geser merupakan salah satu parameter untuk megetahui kondisi tanah serta memperkirakan bahaya gerakan tanah secara spesifik yang berdampak terhadap daya dukung tanah disekitar kawasan (Yusran,2021). Lapisan tanah dengan kepadatan rendah umumnya memiliki daya dukung yang rendah pula, sehingga rawan terhadap terjadinya penurunan pondasi bangunan (Arisona, 2017;Mustika dan Sriyani, 2019). Kajian dalam bentuk pemetaan lapisan tanah dengan menggunakan data Mikrotremor HVSR diperlukan untuk memperoleh gambaran tentang lapisan tanah yang berpotensi tinggi rawan terhadap guncangan gempa bumi.…”
Section: Pendahuluanunclassified
“…The geology of the study area is majorly composed of granitic rock and also its associates -limestone, phyllite, schist and sandstone. The study area also includes a great quantity of major and minor faults as shown in Figure 2a (Arisona et al, 2017).…”
Section: Geology Of Study Areamentioning
confidence: 99%